An English Vocabulary Learning through Word Games: Serendipitous Community Service - Iman, Jaya Nur (Institut Teknologi Nasional, Bandung, 2026)
Mastering English vocabulary is something mandatory in learning integrated English language skill for EFL learners as this could enhance their English competence and performance. This community service was conducted in a serendipitous way in which it was aimed to apply games in teaching English vocabulary. Thirteen female participants were taken conveniently as the sample during the intervention. One orphanage in Southern region of Sumatera, Palembang was accordingly selected for this activity. To assess the EFL participants’ English vocabulary score, a well-designed English vocabulary test was finely administered before and after game-based intervention. The findings showed that using games gave a significant impact on the EFL learners’ English vocabulary mastery as the result of t obtained value was much higher than the t table (10.645 > 2.179) and the p value gained was much lower than .05 (.000 < .05). Overall, some meaningful implications were made to the near future facilitators, relevant researchers, and other EFL learners to integrate games in English vocabulary learning as this creates a more relaxing atmosphere of learning English words.